2019
DOI: 10.1080/13676261.2019.1581361
|View full text |Cite
|
Sign up to set email alerts
|

General and LGBTQ-specific factors associated with mental health and suicide risk among LGBTQ students

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 55 publications
1
62
0
2
Order By: Relevance
“…As the survey is school-based, information on important national, community and household indicators factors were missing, such as socioeconomic status, food security, family risk and protective factors, cultural and religious factors or national political climate. Additionally, in some LMIC where school attendance is A recent systematic review reported higher rates of depression among young lesbian, gay, bisexual, transgender and questioning (LGBTQ) and LGBTQ-factors were associated with suicide risk [41,42]. This may help explain some of the findings regarding bullying, injuries, etc.…”
Section: Discussionmentioning
confidence: 99%
“…As the survey is school-based, information on important national, community and household indicators factors were missing, such as socioeconomic status, food security, family risk and protective factors, cultural and religious factors or national political climate. Additionally, in some LMIC where school attendance is A recent systematic review reported higher rates of depression among young lesbian, gay, bisexual, transgender and questioning (LGBTQ) and LGBTQ-factors were associated with suicide risk [41,42]. This may help explain some of the findings regarding bullying, injuries, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study investigated self-acceptance of sexuality in relation to suicidality and found no significant relationship with suicidal ideation ( r = − .05) or attempts ( r = .10; Hershberger & D’Augelli, 1995 ). It is possible that suicidality may be less strongly associated with self-acceptance than with stressful events, such as LGBQ+ victimization (Gnan et al, 2019 ; Hershberger & D’Augelli, 1995 ). It is also possible that people whose self-acceptance is so problematic that they consider suicide will be less likely to report identifying with a minority sexual orientation in research, and those who completed suicide cannot be included in many research designs.…”
Section: Summary Of Study Findings and Discussionmentioning
confidence: 99%
“…Russell et al analyzed the data covering 245 LGBT youth aged between 21 and 25 and found that victimization at school was linked to high suicidal ideation, reduced self-esteem, and low levels of satisfaction with life [28]. In addition, a UK-based Youth Chances community survey involving 1,948 LGBTQ+ university students examined both general as well as LGBTQ+-specific factors linked to mental health problems, self-harm, suicide risks, and use of mental health services [29]. The findings revealed that negative experiences on account of one's LGBTQ+ identity can be linked to self-harm, heightened suicide risks, and mental health problems [29].…”
Section: Mental Health Issuesmentioning
confidence: 99%
“…In addition, a UK-based Youth Chances community survey involving 1,948 LGBTQ+ university students examined both general as well as LGBTQ+-specific factors linked to mental health problems, self-harm, suicide risks, and use of mental health services [29]. The findings revealed that negative experiences on account of one's LGBTQ+ identity can be linked to self-harm, heightened suicide risks, and mental health problems [29]. A different study also performed a secondary data analysis of 145 LGBT adults aged between 18 and 20 from 59 LGBT college and university student groups.…”
Section: Mental Health Issuesmentioning
confidence: 99%